Modern Technology's role in accounting cost calculation of industrial enterprises: Informatization as a key strategy to improve management efficiency - HuiFang Liang (Heliyon)
The study aims to address challenges encountered by modern industrial enterprises, including inefficient accounting cost calculation, delayed information acquisition, and untimely management decisions. By comprehensively applying modern management, information technology, and cost control methods, this study constructs a real-time cost control model to optimize industrial enterprises. Firstly, the model employs mixed integer linear programming (MILP) to optimize production processes through mathematical modeling. Secondly, it utilizes data mining technology to assist enterprises in cost accounting and efficiency analysis. Big data analysis aids in predicting production process changes and trends, providing data support for management decisions. Intelligent production scheduling and resource optimization are facilitated by artificial intelligence (AI) technology, enabling real-time data collection, processing, and analysis. Finally, the activity-based costing method categorizes, allocates, and measures costs to enhance cost accounting accuracy and efficiency. Research results demonstrate that enterprises adopting the theoretical framework of real-time cost control can enhance the accuracy of cost accounting, cost control efficiency, and overall management effectiveness.